Keterampilan Berbicara Siswa Cerdas Linguistik dan Pengembangannya Di Kelas V SD Birrul Walidain Sragen Tahun Ajaran 2016/ 2017 - Efendi, Bagos Arief, Dr. Achmad Fathoni, M.Pd (2017)
This research aims to describe: 1. How can student speaking skills that have linguistic intelligence. 2. How to implement the development of student speaking skills in. This type of research is qualitative research. Data were analyzed through interactive. Data were analyzed through data reduction steps, the presentation of data, and the withdrawal of the conclusion. Techniques of examination of the validity of the data is done by triangulation of sources and techniques. The results showed that: 1. Speaking Skill intelligent linguistik student in class V showed a. onsonant pronunciation clear, b. Using suppression tone, c. Less effective word choice, d. Good sentence structure, e. Show courage and spirit, f. Speak fluently, g. Speak loudly, h. Using gestures and view eye, i. Mastering topic talks. 2. Implementation of the development of speaking skills using storytelling showed: a. Illustrative understending story, b. Illustrative various story, c. Divide student to be five group, d. Teacher storytelling Malin Kundang, e. Share work student sheet f. Group discusion, g. Teacher shareevaluation question, h. Perceive story.Keyword: speaking skills, linguistic intelligence, talking development